VARIAN IKAN NIKE (Awaous melanocephalus) DAN IKAN CAKALANG (Katsuwonus pelamis) TERHADAP MUTU KERUPUK - Desi Arisanti (UPPM Politeknik Gorontalo, 2017)
the current utilization of nike fish and tuna is still limited to fresh condition. Crackers are a very popular food by all levels of society. Utilization of nike fish and tuna in processed form with longer shelf life has not been done. Nutritional content of both types of fish is a reason in the selection as a basic ingredient in making crackers. The purpose of this research is to know the formulation of nike fish and tuna to the quality of crackers. The observation parameters in this study are the level of favorite or hedonic method, water content, ash content, bloom and texture analizer. The results showed that the average water content of nike fish crackers and skipjack fish from treatment A1 3.3%, treatment A2 3.29%, A3 3.77%. Mean of ash content at treatment of A1 1,97%, treatment of A2 1,55%, treatment of A3 1,58%. The average of A1 is 283,54%, A2 242,75%, A3 182,23%. and the mean of analyzer analyzer test at A1 1185,6%, A2 708,9%, and A3 783,83%. Based on the results and the discussion that has been done on the quality of crackers, it can be concluded that the best formula and liked by the panelists is formula A1